'Mental health day' sickness absence amongst nurses and midwives: workplace, workforce, psychosocial and health characteristics. (5th December 2016) - Lamont, Scott; Brunero, Scott; Perry, Lin; Duffield, Christine; Sibbritt, David; Gallagher, Robyn; Nicholls, Rachel
Abstract: Aim: To examine the workforce, workplace, psychosocial and health characteristics of nurses and midwives in relation to their reported use of sickness absence described as 'mental health days'. Background: The occupational stress associated with the nursing profession is increasingly recognized and nurse/midwifery absenteeism is a significant global problem. Taking a 'mental health day' as sickness absence is a common phenomenon in Australian health care. No previous studies have empirically explored the characteristics of nurses and midwives using such sickness absence. Design: Online cross‐sectional survey. Methods: Survey comprising validated tools and questions on workplace and health characteristics was distributed to nurses and midwives in New South Wales, Australia, between May 2014 ‐ February 2015. Sample characteristics were reported using descriptive statistics. Factors independently predictive of 'mental health day' reportage were determined using logistic regression. Results: Fifty‐four percentage of the n = 5041 nurse and midwife respondents took 'mental health days'. Those affected were significantly more likely to be at younger ages, working shifts with less time sitting at work; to report workplace abuse and plans to leave; having been admitted to hospital in previous 12 months; to be current smokers; to report mental health problems, accomplishing less due to emotional problems and current psychotropic medication use. Conclusion: Specific characteristics of nurses and midwives who report taking 'mental health day' sickness absence offer healthcare administrators and managers opportunities for early identification and intervention with workplace measures and support frameworks to promote well‐being, health promotion and safety.